Investment Treaty Arbitration as Public International Law : Procedural Aspects and Implications - De Brabandere, Eric (Cambridge : Cambridge University Press, 2014)
Investment treaty arbitration is fast becoming one of the most common methods of dispute settlement in international law. Despite having ancient roots, tensions remain between the private interests in international investment relations and the public international law features of the arbitral procedure. This book, which presents an account of investment treaty arbitration as a part of public international law - as opposed to commercial law - provides an important contribution to the literature on this subject. Eric De Brabandere examines the procedural implications of conceiving of investment treaty arbitration in such a way, with regard to issues such as the principles of confidentiality and privacy, and remedies. The author demonstrates how the public international law character of investment treaty arbitration derives from, and has impacted upon, the dispute settlement procedure.
Title from publisher's bibliographic system (viewed on 03 May 2017).
Keywords: International commercial arbitration; Investments, Foreign (International law); Commercial treaties